Shifting paradigm of the university library in the evolving landscape of higher education - Wijetunge, Pradeepa (My University, 2014)
There are many changes in the landscape of higher education in Sri Lanka, but this paper selected the introduction of Outcomes-Based Education (OBE) through Student-Centred Learning (SCL) as its scope considering its significant impact on the university libraries. A brief account of the OBE, SCL and the symbiosis between the two is followed by the challenges encountered by the teachers and students practicing SCL (other stakeholders are not considered here to limit the scope of the paper). The crucial role that can be played by the university library in the SCL environment is discussed with the emphases on providing access to increased volume of information needed, sharing information and other resources cost effectively, and enhancing information management skills through information literacy.
Keywords: Shifting paradigm of the university library in the evolving landscape of higher education